Thromboelastography Maximum Amplitude Predicts Postoperative Thrombotic Complications Including Myocardial Infarction - Douglas J. McCrath; Elisabetta Cerboni; Robert J. Frumento; A. Hirsh; Elliott Bennett‐Guerrero (2005)
In Brief Postoperative thrombotic complications increase hospital length of stay and health care costs. Given the potential for thrombotic complications to result from hypercoagulable states, we sought to determine whether postoperative blood analysis using thromboelastography could predict the occurrence of thrombotic complications, including myocardial infarction (MI). We prospectively enrolled 240 patients undergoing a wide variety of surgical procedures. A cardiac risk score was assigned to each patient using the established revised Goldman risk index. Thromboelastography was performed immediately after surgery and maximum amplitude (MA), representing clot strength, was determined. Postoperative thrombotic complications requiring confirmation by a diagnostic test were assessed by a blinded observer. Ten patients (4.2%) suffered a total of 12 postoperative thrombotic complications. The incidence of thrombotic complications with increased MA (8 of 95 = 8.4%) was significantly (P = 0.0157) more frequent than that of patients with MA ≤68 (2 of 145 = 1.4%). Furthermore, the percentage suffering postoperative MI in the increased MA group (6 of 95 = 6.3%) was significantly larger than that in the MA ≤68 group (0 of 145 = 0%) (P = 0.0035). In a multivariate analysis, increased MA (P = 0.013; odds ratio, 1.16; 95% confidence interval, 1.03–1.20) and Goldman risk score (P = 0.046; odds ratio, 2.39; 95% confidence interval, 1.02–5.61) both independently predicted postoperative MI. A postoperative hypercoagulable state as determined by thromboelastography is associated with postoperative thrombotic complications, including MI, in a diverse group of surgical patients. IMPLICATIONS: Postoperative thrombotic complications increase hospital length of stay and health care costs. In a cohort study of 240 patients undergoing a wide variety of surgical procedures, we describe how a point-of-care test (thromboelastography maximum amplitude) at the end of surgery can be used to predict thrombotic complications, including myocardial infarction.